Kajian Cost Benefit Instalasi Sistem Penerangan Jalan Umum Tenaga Surya (Pju-Ts) Di Daerah Tertinggal - Adiningsih S, Sri Hutami; Nurwahida (PT. Lontara Digitech Indonesia, 2025)
This study aims to assess the feasibility of the economic installation system of Solar Street Lighting (PJU-TS) on Sapuka Island, Liukang Tangaya District, Pangkep Regency—an island region that is categorized as a disadvantaged region. The study uses a cost-benefit analysis (CBA) approach to produce the economic efficiency of the PJU-TS project. Based on the calculation of Net Present Value (NPV), Benefit-Cost Ratio (BCR), and Payback Period, the results show that this project is economically feasible and provides significant social benefits. These findings support the development of renewable energy as a lighting solution in island areas that are difficult to reach by conventional electricity networks.